RECONSTRUCTION OF MUHAMMAD IQBAL'S ISLAMIC THOUGHT: A PILLAR OF MODERN ISLAMIC THINKING - Yossar, Yossar; Nur Hakima Akhirani; Mira Yanti Lubis; Fithri Choirunnisa Siregar; Sutan Botung Hasibuan; Rusydi AM; Riki Saputra (PT. Jurnal Center Indonesia Publisher, 2025)
Muhammad Iqbal emerged during a period of intellectual stagnation in the Muslim world in the early 20th century, introducing a fresh and visionary idea: the reconstruction of religious thought. In his seminal work, The Reconstruction of Religious Thought in Islam, Iqbal proposed a way out of this stagnation by revitalizing the Islamic intellectual heritage while engaging in a critical dialogue with modernity. This study aims to examine the key concepts of Iqbal's project, including his critique of Greek philosophy, his dynamic view of ijtihad (legal reasoning), his theory of the